Regional differences in the incidence of self-reported type 2 diabetes in Germany: results from five population-based studies in Germany (DIAB-CORE Consortium). Issue 11 (29th July 2014) - Schipf, Sabine; Ittermann, Till; Tamayo, Teresa; Holle, Rolf; Schunk, Michaela; Maier, Werner; Meisinger, Christine; Thorand, Barbara; Kluttig, Alexander; Greiser, Karin Halina; Berger, Klaus; Müller, Grit; et al.
Abstract : Background: Population-based data are paramount to investigate the long-term course of diabetes, for planning in healthcare and to evaluate the cost-effectiveness of primary prevention. We analysed regional differences in the incidence of self-reported type 2 diabetes mellitus in Germany. Methods: Data of participants (baseline age 45–74 years) from five regional population-based studies conducted between 1997 and 2010 were included (mean follow-up 2.2–7.1 years). The incidence of self-reported type 2 diabetes mellitus at follow-up was compared. The incidence rates per 1000 person-years (95% CI) and the cumulative incidence (95% CI) from regional studies were directly standardised to the German population (31 December 2007) and weighted by inverse probability weights for losses to follow-up. Results: Of 8787 participants, 521 (5.9%) developed type 2 diabetes mellitus corresponding to an incidence rate of 11.8/1000 person-years (95% CI 10.8 to 12.9). The regional incidence was highest in the East and lowest in the South of Germany with 16.9 (95% CI 13.3 to 21.8) vs 9.3 (95% CI 7.4 to 11.1)/1000 person-years, respectively. The incidence increased with age and was higher in men than in women. Conclusions: The incidence of self-reported type 2 diabetes mellitus shows regional differences within Germany. Prevention measures need to consider sex-specific differences and probably can be more efficiently introduced toward those regions in need.